Measuring color techniques for forensic comparative analyses of geological evidence - Roberta Somma; Sebastiano Ettore Spoto; Marcello Raffaele; Fabio Salmeri (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2023)

(untitled)
In Forensic Geology, color examination of sediments and soils is one of the first analyses for exclusionary/comparative purposes. Forensic colorimetry deals with the examination of the color of physical evidence related to criminal investigations. Color of soils and sediments has always been considered an essential parameter and one of the most common and crucial visually physical property for characterizing, describing, and comparing these geological materials, since the first steps of forensic investigations. This parameter may be evaluated both qualitatively and quantitative. In forensic comparative analyses of sediments and soils, most of the colorimetric methods are nowadays computational. These computational instruments, provided of standards and standardized illumination conditions, may obtain very high-resolution and non-destructive quantitative data. When adapted to sedimentological applications for forensic purposes, photometric instrumentations are powerful tools due to their low purchase and maintenance costs. Moreover, some devises are also portable and easily used at the crime scene. Recent advances in the colorimetry research showed as also the simple use of digital devises, such as low-cost flatbed scanners, may be easily applied for the color examination of acquired color images of sediments and soils, if calibrated with standards, as reference charts or database. The results of a simulated forensic casework devoted to the comparative analysis of the color of soils, acquired by means low-cost flatbed scanner, confirmed previous results on this useful application.